A Case–Control Study of Risk Factors for Bovine Cysticercosis in Danish Cattle Herds. (2nd August 2012) - Calvo‐Artavia, F. F.; Nielsen, L. R.; Dahl, J.; Clausen, D. M.; Graumann, A. M.; Alban, L.
Summary Bovine cysticercosis (BC) is a zoonotic, parasitic infection in cattle. Under the current EU meat inspection regulation, every single carcass from all bovines above 6 weeks of age is examined for BC. This method is costly and makes more sense in countries with higher number of BC‐infected animals than in countries with few lightly infected cases per year. The aim of the present case–control study was to quantify associations between potential herd‐level risk factors and BC in Danish cattle herds. Risk factors can be used in the design of a risk‐based meat inspection system targeted towards the animals with the highest risk of BC. Cases (n = 77) included herds that hosted at least one animal diagnosed with BC at meat inspection, from 2006 to 2010. Control herds (n = 231) consisted of randomly selected herds that had not hosted any animals diagnosed with BC between 2004 and 2010. The answers from a questionnaire and register data from the Danish Cattle Database were grouped into meaningful variables and used to investigate the risk factors for BC using a multivariable logistic regression model. Case herds were almost three times more likely than control herds to let all or most animals out grazing. Case herds were more than five times more likely than control herds to allow their animals access to risky water sources with sewage treatment plant effluent in proximity. Case herds were also more likely to share machinery or hire contractors than control herds. The risk decreased with increasing herd size probably because the larger herds generally tend to keep cattle indoors in Denmark. The results are useful to guide future data recording that can be supplied by the farmer as food chain information and then be used for differentiated meat inspection in low‐ and high‐risk groups, enabling development of risk‐based meat inspection systems.